A high-performance millirobot for swarm-behaviour studies: Swarm-topology estimation. (13th December 2019) - Kim, Justin Y; Kashino, Zendai; Pineros, Laura Marcela; Bayat, Sayeh; Colaco, Tyler; Nejat, Goldie; Benhabib, Beno
In this article, we present a novel high-performance millirobot ( m illi- rob ot- To ronto), designed to allow for the testing of complex swarm-behaviours, including human–swarm interaction. m illi- rob ot- To ronto, built only with off-the-shelf components, has locomotion, processing and sensing capabilities that significantly improve upon existing designs, while maintaining one of the smallest footprints among current millirobots. As complementary software to this hardware development, herein, we also present a new global swarm-topology estimation algorithm. The method is novel in that it uniquely fuses incomplete location data collected by the individual robots in a distributed manner to optimally estimate the topology of the overall swarm using a centralized computer. It is a generalized technique usable by any swarm comprising robots capable of collecting location estimates of neighbouring robots. Numerous experiments, evaluating the performance of m illi- rob ot- To ronto and the proposed optimal swarm-topology estimation algorithm, are also included.